2017
DOI: 10.1002/hrdq.21284
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Study on the Consequences of Intensive Working

Abstract: The nomological network of intensive working, or ‘workaholism’, is unclear. Taking a theoretically driven social constructivist approach, anchored in the field of human resource development (HRD), this study sought to explore how male intensive workers understand the consequences of their work patterns with respect to the experience of satisfaction and dissatisfaction in the work and nonwork domains. Deploying an interpretivist paradigm, data from 30 interviews were analyzed. These comprised 10 people who cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
11
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 128 publications
(185 reference statements)
0
11
3
Order By: Relevance
“…with growing interest in human-oriented perspectives (Han, Chae, Han, & Yoon, 2017), such as work stress (Anthony-McMann, Ellinger, Astakhova, & Halbesleben, 2017), excessive work (Kirrane, Breen, & O'Connor, 2017), and employee wellbeing (Tonkin, Malinen, Näswall, & Kuntz, 2018). Although the concept of workaholism first appeared several decades ago (Oates, 1968(Oates, , 1971, it is an emerging topic that has received increasing attention in organizational research and has great implications for HRD.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…with growing interest in human-oriented perspectives (Han, Chae, Han, & Yoon, 2017), such as work stress (Anthony-McMann, Ellinger, Astakhova, & Halbesleben, 2017), excessive work (Kirrane, Breen, & O'Connor, 2017), and employee wellbeing (Tonkin, Malinen, Näswall, & Kuntz, 2018). Although the concept of workaholism first appeared several decades ago (Oates, 1968(Oates, , 1971, it is an emerging topic that has received increasing attention in organizational research and has great implications for HRD.…”
mentioning
confidence: 99%
“…Over the past few decades, scholars have dedicated a significant amount of time to understanding work involvement as a key factor affecting employee well-being. Since Russ-Eft’s (2001) call for research, human resource development (HRD) has discussed the outcomes of job involvement beyond performance and productivity with growing interest in human-oriented perspectives (Han, Chae, Han, & Yoon, 2017), such as work stress (Anthony-McMann, Ellinger, Astakhova, & Halbesleben, 2017), excessive work (Kirrane, Breen, & O’Connor, 2017), and employee well-being (Tonkin, Malinen, Näswall, & Kuntz, 2018). Although the concept of workaholism first appeared several decades ago (Oates, 1968, 1971), it is an emerging topic that has received increasing attention in organizational research and has great implications for HRD.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…More recent studies also reported inconclusive results. For example, Balducci et al (2018) found that work addiction was related to negative job-related affect, while Kirrane, Breen, & O'Connor (2017) in a qualitative investigationfound that work addicted report higher levels of job satisfaction, a finding corroborated by coworkers. Overall, it is clear that there is a need for further research to clarify the work-related affective experiences of work addicted.…”
Section: Theoretical Framework and Hypothesesmentioning
confidence: 92%
“…Additionally, and importantly, the heavy work investment characterizing workaholism does not seem to be associated with higher job performance [ 14 ]—although evidence on the relationship between workaholism and objective performance criteria is still sparse. Thus, the available research suggests—with only some exceptions [ 15 ]—that workaholism has few advantages for both individuals and organizations, and a number of disadvantages and that it therefore should be prevented as much as possible.…”
mentioning
confidence: 99%